Makna Simbolik Tradisi Sinunö Falöwa Dalam Adat Pernikahan Masyarakat Nias di Kota Gunung Sitoli - Shadafira, Zahratul Jannah (Jurnal Psikotes, 2024)
This research aims to find out the Sinunö falöwa tradition in the wedding customs of the Nias community in Gunungsitoli City, to find out the symbols presented in the Sinunö Falöwa tradition in the wedding customs of the Nias community in Gunungsitoli City, to find out the meaning of each symbol of the Sinunö Falöwa tradition in the community's wedding customs. Nias in Gunungsitoli City. This research method uses a qualitative approach with interview techniques. The results of the research show that the position of sinunö falöwa at a wedding party has to this day greatly influenced the purity of a traditional Nias wedding party, although currently there has begun to be a reduction in its meaning and method of use due to the perpetrators themselves reducing the time/process of carrying out the wedding party. and not only that, modern conditions now make it possible to use means of transportation so that the tome party no longer walks to the sowatö's house, which results in very few bölihae wedding songs being performed. Wedding Songs in the Nias Community in Musicological and Textual Descriptions", it can be concluded that Sinunö falöwa namely bölihae, fangowai and hendri-hendri are important vocal music and are used at weddings based on customs in Nias. The three types of vocal music in Sinunöfalowa use text compositions that tend to change in the next melody, where the melody of the song can be said to consist of repetitions with the same or almost identical patterns. the same, while the text changes or tends to be new (stofic). And it can also be said that this song is sung using a responsive (call and respond) technique.